Pediatric gastrointestinal tuberculosis with hematochezia and polyarthritis: An unusual presentation - Begum, Suraiya; Fatema, Kanij; Rahman, Shahana Akhter (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Tuberculosis may present with variable symptoms and signs, sometimes presentations are unusual. An eight year old boy was admitted with the complaints of low grade fever, weight loss, abdominal pain, hematochezia and polyarthritis. Colonic biopsy was suggestive of tuberculosis and Gene-Xpart of sputum showed of multidrug resistant tuberculosis. We are reporting a case presented with hematochezia and poloyarthritis, an unusual presentation who was subsequently diagnosed as a case of multi drug resistant intestinal tuberculosis.